KECENDERUNGAN MAHASISWA UIN SAIZU DALAM MENGGUNAKAN SUMBER INFORMASI - Kusuma Ningrum, Ayuk; Hastuti, Ulfah Rulli (IAIN Ponorogo, 2025)
The primary responsibility of librarians is to manage information resources in the library to meet users' needs. Most students at UIN Saizu belong to the millennial and Generation Z groups, who are highly dependent on information technology. This study aims to examine the tendencies of UIN Saizu students in utilizing information sources. A mixed-methods approach was employed, combining qualitative data collected through interviews with selected informants and quantitative data from 482 respondents. The results show that UIN Saizu students predominantly rely on online journals (51.7%) as their main reference source, followed by textbooks (23.2%), e-books (17%), institutional repositories (5.6%), and lecturers' scholarly works (2.5%). The majority of students who access online journals use Google Scholar as their primary research tool. The findings of this study reflect students information-seeking preferences for easily accessible digital sources. This study contributes to a better understanding of student preferences in selecting academic information sources and may serve as a reference for the development of library services and information literacy programs.